Cultural Dynamics and Psychological Perspectives: Unraveling the Human Psyche in South Korea - Hee Young (International Journal of Science and Society, 2023)
This article delves into the intricate interplay between cultural dynamics and psychological perspectives within the context of South Korea. Rooted in a rich tapestry of Confucian values, modernization, and global influences, South Korean society undergoes continuous transformations that shape the perceptions and behaviors of its people. The exploration begins by examining the deep-seated Confucian heritage, collectivism, and social hierarchy that influence individual and group psychology. Traditional values, norms, and practices are unveiled as influential factors in shaping psychological attitudes and behaviors, with a particular focus on family-centered values, collectivism, and the unique concept of "han". Modernization, urbanization, and globalization are then analyzed for their role in reshaping traditional cultural dynamics and their implications for mental health and well-being. The narrative shifts towards the effects of technology, media, and exposure to Western values on different generations, resulting in nuanced psychological perspectives. The emergence of a culture of competition, high expectations, and the "exam hell" phenomenon in South Korean society is explored, highlighting the stress, anxiety, and mental health implications that ensue.